Character association for fruit yield and yield traits in Salacia chinensis L.: A threatened medicinal plant - Laxmi Mastiholi; Raviraja Shetty, G and; P. E. Rajasekharan (Electronic Journal of Plant Breeding, 2018)
An experiment was undertaken to study the correlation and path analysis in thirteen accessions of Salacia chinensis L. Correlation study revealed that plant height, plant spread, fruit diameter, fruit weight, seed diameter, seed length and seed weight had positive significant correlation with fruit yield per plant at both genotypic and phenotypic levels. According to path analysis the seed length, plant height and seed diameter recorded positive and high direct effects on fruit yield per plant while, seed weight, fruit length and leaf length had high negative direct effects on fruit yield per plant. Thus based on correlation and path analysis, the traits viz., plant height, plant spread, fruit diameter, fruit weight, seed diameter, seed length and seed weight can be considered as selection indices for high yield.